The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/ndt/gfx355
|View full text |Cite
|
Sign up to set email alerts
|

Changes in co-morbidity pattern in patients starting renal replacement therapy in Europe—data from the ERA-EDTA Registry

Abstract: More than two-thirds of patients initiating RRT in Europe have at least one co-morbidity. With the rising age at the start of RRT over the last decade, there have been changes in the co-morbidity pattern: the prevalence of cardiovascular co-morbidities decreased, while the prevalence of DM and malignancy increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
2
22
1
2
Order By: Relevance
“…The present study identified hypertension (87.2%, n = 129) as the most common comorbidity, followed by anemia (48.6%, n = 72), diabetes (47.3%, n = 70), dyslipidemia (19.6%, n = 29), and peptic ulcer (19.6%, n = 29). The discovery that hypertension and diabetes were among the most common comorbidities was in agreement with several related studies [4,13,30]. Notably, this study discovered that anemia was the second most common comorbidity, which is in agreement with the findings of another study [31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study identified hypertension (87.2%, n = 129) as the most common comorbidity, followed by anemia (48.6%, n = 72), diabetes (47.3%, n = 70), dyslipidemia (19.6%, n = 29), and peptic ulcer (19.6%, n = 29). The discovery that hypertension and diabetes were among the most common comorbidities was in agreement with several related studies [4,13,30]. Notably, this study discovered that anemia was the second most common comorbidity, which is in agreement with the findings of another study [31].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, WBC counts and HBC, HCT, albumin, total protein, and creatinine levels were found to be variables of critical significance. Because studies have suggested that most patients with ESKD can develop one or multiple comorbidities [12,13], the 3 most common comorbidities, namely hypertension (87.2%), anemia (48.6%), and diabetes (47.3%), were analyzed in this study. The other comorbidities that were studied were dyslipidemia and peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] However, because of the multifactorial nature of excess cardiovascular mortality in this patient group, the observed decrease may be explained by multiple changes instead of 1 single intervention. Ceretta et al 31 showed that in Europe between 2005 and 2014, the percentage of patients with ischemic heart disease as a comorbidity at the start of KRT decreased, indicating that patients start dialysis in better cardiovascular health, which may have contributed to the improved survival observed in this study. Furthermore, better management of dialysis patients with myocardial infarction or stroke in the last decades may partly explain the decrease in excess atheromatous CVD mortality.…”
Section: Trends In Dialysis Patientsmentioning
confidence: 53%
“…This increase did not come to a halt in the $75 years KRT cohort, despite the declining male-to-female ratio in the general population. The greater comorbidity burden among males may play an important role (28). Further investigations in the elderly population with advanced CKD (stage 4 or 5) will be useful in identifying potentially protective biologic factors and perhaps also behavioral factors in women underlying this phenomenon.…”
Section: Discussionmentioning
confidence: 99%